DETERMINATION OF ALLANTOIN LEVELS AS A RESULT OF OPTIMIZATION OF IONIC LIQUID-ULTRASOUND ASSISTED EXTRACTION OF COMFREY LEAVES BY TLC-DENSITOMETRY - Andika Purnomo; Abdul Mun'im; Hayun Hayun (BIOVALENTIA: Biological Research Journal, 2022)
Allantoin is a compound contained in comfrey leaves. This research aims to obtain optimal condition parameters of ionic liquid-ultrasound-assisted extraction (IL-UAE) comfrey leaves to attract allantoin compounds. Comfrey leaves are extracted with eight ionic liquids by ultrasound-assisted extraction (UAE) and screened for allantoin levels. The best ionic liquid from the screening results is optimized response surface methodology (RSM) with Box-Behnken design with three factors and three levels to determine the optimum extraction conditions for allantoin levels. Determination of levels is carried out with TLC densitometry. The results of the IL screening obtained [HMIM]Cl as the best  IL in the evaluation of optimization of extraction parameters. The results of optimization of extraction condition parameters [HMIM]Cl obtained the highest allantoin levels on the sixth run of 306.396 μg / g of powder at the ratio of solvents to powders of 10 mL / g, concentrations [HMIM] Cl 1 mol / L and extraction time of 30 minutes.